Relasi Kiai Dalam Penyelesaian Sengketa Waris di Madura - Gufron, Guforn (Institut Agama Islam Negeri (IAIN) Syekh Nurjati Cirebon, 2025)
Abstract Indonesia is a country that adheres to legal pluralism in the application of inheritance law. This choice has an impact on the resolution of various inheritance disputes, including those carried out by the majority of people in Madura. This study aims to determine three important points. (1) the factors causing the Madurese people to choose customary inheritance law in the distribution of inheritance assets (2), what are the techniques for resolving inheritance disputes in Madura? And (3) how is the relationship between the kiai in resolving inheritance disputes in Madura? This research is qualitative, by combining field data obtained through a series of interviews, in-depth observations. Then descriptive-analytical is carried out by analyzing the findings of data in the field using a legal sociology approach. The findings of this study are as follows. First, Madurese society in inheritance practices generally uses legal pluralism. Namely Islamic law, positive law, and customary law. However, the majority of Madurese people use customary inheritance law by dividing equally. Second, there are three models of practice in resolving inheritance disputes carried out by Madurese society in general. Namely by means of family deliberation to reach consensus, then mediation involving a kiai as a mediator, and finally taking the legal route. Third, the figure of the kiai in Madura has an important position and role in society, especially acting as a mediator when an inheritance dispute occurs. Such a pattern can create a relationship that is not only limited to patron-client, but also a broader reciprocal relationship between the two that is mutually beneficial. Keywords: Madurese Customary Inheritance Law, Kiai Relations, Inheritance Disputes